Management theory in action : - Kessler, Eric H. (Palgrave Macmillan, 2010)
Bridging the divide between management theory and practice is an obstacle for many business school graduates. Management Theory in Action provides, in an easy-to-relate manner, real-life accounts of how actual people have used classroom-taught theories and skills to better understand and perform at their jobs. Practical guidelines are included to help the reader use these lessons to become a stronger individual, engage in more effective interactions, and build more productive workplace environments.